2006
DOI: 10.1016/j.molcel.2006.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Localization of MCM2-7, Cdc45, and GINS to the Site of DNA Unwinding during Eukaryotic DNA Replication

Abstract: Little is known about the architecture and biochemical composition of the eukaryotic DNA replication fork. To study this problem, we used biotin-streptavidin-modified plasmids to induce sequence-specific replication fork pausing in Xenopus egg extracts. Chromatin immunoprecipitation was employed to identify factors associated with the paused fork. This approach identifies DNA pol alpha, DNA pol delta, DNA pol epsilon, MCM2-7, Cdc45, GINS, and Mcm10 as components of the vertebrate replisome. In the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
299
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(317 citation statements)
references
References 34 publications
14
299
0
4
Order By: Relevance
“…Chromatin immunoprecipitation (ChIP) was performed as described (Pacek et al , 2006). Briefly, reaction samples were crosslinked with formaldehyde, sonicated to yield DNA fragments of roughly 100–500 bp, and immunoprecipitated with the indicated antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…Chromatin immunoprecipitation (ChIP) was performed as described (Pacek et al , 2006). Briefly, reaction samples were crosslinked with formaldehyde, sonicated to yield DNA fragments of roughly 100–500 bp, and immunoprecipitated with the indicated antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…However, the area spanned by six patches is rather broad to accommodate a single protein, and thus it is likely that multiple proteins bind to these patches. Thus, based on structural and genetic analyses, we propose that this region within GINS might mediate the assembly of proteins in an RPC (Calzada et al 2005;Gambus et al 2006;Pacek et al 2006).…”
Section: Conserved Surface Regions With Functional Significancementioning
confidence: 99%
“…In budding yeast, chromatin immunoprecipitation analysis identified the GINS complex as a part of the replisome that contains MCM2-7, Cdc45, Pols ␣ and , and other replication regulation factors (Calzada et al 2005). The vertebrate replisome at the paused fork also contained GINS, along with Pols ␣ and , MCM2-7, Cdc45, and MCM10 (Pacek et al 2006). Moreover, a proteomics study in budding yeast showed that the GINS complex allows the MCM helicase to stably associate with Cdc45 in replisome progression complexes (RPCs) during and after the initiation of replication (Gambus et al 2006;Kanemaki and Labib 2006).…”
mentioning
confidence: 99%
“…After loading onto DNA, the MCM complex interacts with CDC45 and GINS to unwind DNA at the replication fork (Gambus et al, 2006;Moyer et al, 2006;Pacek et al, 2006;Chang et al, 2007). Each of the MCM2 to MCM7 proteins contains several highly conserved sequence features, including an ATP hydrolysis domain, an Arg finger motif, and a zinc-binding domain (Maiorano et al, 2006).…”
mentioning
confidence: 99%